2006
DOI: 10.1111/j.1540-8191.2006.00208.x
|View full text |Cite
|
Sign up to set email alerts
|

A Bicuspid Pulmonary Valve Associated with Tetralogy of Fallot

Abstract: Congenitally bicuspid pulmonary valves are uncommon. When they occur, it is usually in association with other congenital cardiac lesions, most often a tetralogy of Fallot. We present a rare case of a patient with a congenitally bicuspid pulmonary valve who had pulmonary valve and RVOT reconstruction. The patient did well for 17 years, but needed further reconstruction when the pulmonary valve started getting stenosed and RV pressures went up significantly. The pulmonary valve showed fibroses, thickening, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The true incidence of bicuspid pulmonary valve could be underestimated owing to difficulty in visualising the pulmonary valve on conventional two-dimensional echocardiography. Improper fusion or dedifferentiation of the endocardial cushion is responsible for abnormal semilunar valves and so a bicuspid pulmonary valve is more often associated with other congenital abnormalities such as tetralogy of Fallot or ventricular septal defect ( 2 ). As most patients with bicuspid pulmonary valves are asymptomatic, the diagnosis is often made incidentally after suspicious auscultatory findings and subsequent imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The true incidence of bicuspid pulmonary valve could be underestimated owing to difficulty in visualising the pulmonary valve on conventional two-dimensional echocardiography. Improper fusion or dedifferentiation of the endocardial cushion is responsible for abnormal semilunar valves and so a bicuspid pulmonary valve is more often associated with other congenital abnormalities such as tetralogy of Fallot or ventricular septal defect ( 2 ). As most patients with bicuspid pulmonary valves are asymptomatic, the diagnosis is often made incidentally after suspicious auscultatory findings and subsequent imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented that BPV were common in TOF patients [Nair, Thangaroopan, Cunningham et al (2006);McAleer, Kort, Rosenzweig et al (2001); Chacko, Chiramel, Vimala et al 2017]. Their data reported that 81% of bicuspid valves did not have a median raphe [Chacko, Chiramel, Vimala et al (2017)].…”
Section: The Leaflets Of Pvmentioning
confidence: 98%
“…Its morphologic feature is the presence of only two pulmonary leaflets instead of the normal tri-leaflet. Congenitally BPV are uncommon and the occurrence is often associated with tetralogy of Fallot (TOF) [Nair, Thangaroopan, Cunningham et al (2006);McAleer, Kurt, Rosenzweig et al (2001)]. In the reports by Winn et al [Winn and Hutchins (1973)] and Rao et al [Rao, Anderson and Edwards (1971)].…”
Section: Introductionmentioning
confidence: 99%
“…BPV is a very rare congenital abnormality usually associated with other congenital heart diseases such as tetralogy of Fallot, pulmonary stenosis, and transposition of the great vessels. 1) Interestingly, this case is the BPV accompanied by ASD. Generally, it's difficult or impossible to observe pulmonic valve directly in 2-dimensional TTE.…”
mentioning
confidence: 88%